Assessment of the arrival signatures of the March 2012 CME–CME interaction event with respect to Mercury, Venus, Earth, STEREO-B, and Mars locations - Soni, Shirsh Lata; Selvakumaran, R.; Thampi, R. Satheesh (Frontiers in Astronomy and Space Sciences, 2023)
In March 2012, favorable positions of Mercury, Venus, Earth, Mars, and STEREO-B in the inner Solar System provided an opportunity to understand the global structure and the propagation of two coronal mass ejections (CMEs) across the inner Solar System. On 7 March 2012, the Sun ejected two very fast CMEs from the solar active region NOAA AR11489, which were accompanied by two X-class flares. Initialization and subsequent fast expansion from lower coronal heights of flux rope structures were detected as their early eruption signatures in Solar Dynamics Observatory (SDO) observations. White-light observations have been imaged using SOHO/LASCO and STEREO/SECCHI/COR2 and followed from 00:24 UT on 7 March 2012. We examined the kinematics of the reported CMEs and found a significant exchange of momentum and kinetic energy during the interaction, indicating that the collision was almost inelastic. Furthermore, we observed the arrival of this merged CME event at different distances in the inner Solar System and compared the arrival time with other models. The reported event arrived on Mercury at 04:30 UT; Venus, at 13:28 UT on 7 March 2012; and it took roughly 36 h to reach STEREO-B on 08 March, 03:36 UT. The arrivals at Mercury and Venus are observed in the magnetometer measurements onboard MESSENGER and Venus Express (VEx), respectively. A powerful interplanetary shock was observed on 08 March, 10:19 UT at Earth around 30 h after the two X-class flares and CMEs’ eruption. Subsequently, a south-directed interplanetary magnetic field (IMF) was observed on Earth, indicating the arrival of an interplanetary coronal mass ejection (ICME). This event caused the sudden storm commencement and development of one of the major intense geomagnetic storms of SC 24, with a minimum Dst value of −148 nT. The observations by the Mars Express (MEX) mission indicated the arrival of a merged CME ∼2.5 days after its initial observation at Sun. We have analyzed the evolution of these CMEs and their propagation in the inner heliosphere and arrival signatures at four planetary locations. The propagation and arrival signatures are compared to simulations using the WSA-ENLIL + Cone model and the drag-based model at various vantage points. The study showcases the importance of multi-vantage point observations in understanding the propagation of CMEs and their interactions.